Detection of Water Clarity Level with OpenCV Image Processing Method - Maharani, Siti Mutia; Ramadhan, Yogi Reza; Pranoto, Kirana Astari; Ma’arif, Alfian; Caesarendra, Wahyu; Zy, Ahmad Turmudi (DPPM Universitas Pelita Bangsa, 2023)
Water is the most important compound for the survival of living organisms on Earth. Clean water is essential for human activities. Clean water is characterized by various physical parameters, one of which is water clarity or turbidity. Image processing can be implemented to determine the clarity of water. Advances in image processing technology have made it possible to detect objects and colors in them, supported by libraries such as OpenCV, which provides color spaces. Thus, this research experimentally detects the clarity of water using the HSV and HSL color spaces. This research show significant differences in color for different levels of water clarity using the HSV and HSL color spaces.